The impact of advanced negotiation skills on conflict resolution in workplace environments - Pylypets, Mariia; Petrů, Jaroslav; Pöschl, Carsten; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates the role of advanced negotiation skills in resolving workplace conflicts within multinational IT organizations. Using a qualitative methodology, 15 in-depth interviews were conducted with professionals across diverse roles in a leading IT company and analyzed using Condens software to identify key themes and behavioral patterns. This study uniquely addresses the understudied digital and multicultural contexts within IT environments, providing novel insights into how negotiation skills adapt in virtual and cross-cultural interactions. Findings reveal that emotional intelligence, cultural awareness, and structured communication strategies are crucial in overcoming power asymmetries and fostering psychological safety during digitally mediated conflict resolution. The research concludes that strengthening these competencies can significantly enhance collaboration, communication, and employee satisfaction in global hybrid teams.
Vedoucí práce: Jaroslav Petrů
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses